Constraints on Canadian Arctic maritime connections. Issue 2 (June 2017) - Giguère, Marie-Andrée; Comtois, Claude; Slack, Brian
Highlights: We present the physical characteristics of Canadian Arctic waters. We analyse vessel types and ownership structure of ships sailing in Canada's northern waters as well as the cargo types and their tonnages. Examination of changes in network structure of different commodity groups provides evidence of diversity in the patterns of trade in Arctic waters. Market changes, regulatory regimes and risk remain key challenges for Trans-Polar developments through the North West Passage. Abstract: Sea-ice retreat suggests the possibility of future safe and efficient Arctic marine transportation. The paper first demonstrates that maritime passages in the Canadian Arctic archipelago are complex and include several routeways. This is followed by an analysis of the vessel types and ownership structure of ships sailing in Canada's northern waters as well as the cargo types and their tonnages. This leads into a detailed examination of shipping route patterns and their changes over the past decade. The network structure of different commodity groups provides evidence of diversity in the patterns of trade in Arctic waters between Canadian and foreign fleets. In assessing future trends, the paper identifies key challenges in terms of market changes, regulatory regimes and risk.